2019
DOI: 10.21608/epsj.2019.35016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Supplementation of Different Levels of Thyme and Its Essential Oils on Performance, Blood Parameters, Metabolic and Immune Response of Broiler Chickens

Abstract: The aim of this study was to investigate the effects of dietary supplementation with three levels of thyme (5, 10 and 15 g/kg) and its essential oils (0.5, 1.0 and 1.5 g/kg) on growth performance, blood profiles, immune response and antioxidant status in broiler chickens. A total of one hundred-forty day-old unsexed broiler chicks were randomly allotted to 7 equal groups, each with 4 replicates, and kept in battery cages. Feed and water were offered ad libitum till the termination of the trial at 6 weeks of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The data in the literature on the effect of essential oils on the biometrics of the gastrointestinal tract of birds is still very controversial. Contrary to the present study, [55] found that quails that received thyme essential oil as a phytogenic additive had a larger intestine length and weight than the control treatment. Çabuk et al [56] reported that the blend of essential oils from Origanum sp., Laurus nobilis L., Salvia triloba L., Myrtus communis, Foeniculum vulgare, and Citrus sp.…”
Section: Discussioncontrasting
confidence: 99%
“…The data in the literature on the effect of essential oils on the biometrics of the gastrointestinal tract of birds is still very controversial. Contrary to the present study, [55] found that quails that received thyme essential oil as a phytogenic additive had a larger intestine length and weight than the control treatment. Çabuk et al [56] reported that the blend of essential oils from Origanum sp., Laurus nobilis L., Salvia triloba L., Myrtus communis, Foeniculum vulgare, and Citrus sp.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have documented the effects of dietary EOs, individually or in combinations, on the performance of poultry and swine breeding but with varying and conflicting results [33][34][35]. Earlier, Saleh et al [36] reported that dietary supplementation of thyme and ginger oil individually at dose levels up to 300 g/ton did not affect growth or feed efficiency in broiler chicken. In a review, Zeng et al [37] summarized results from 12 trials on broiler chicken involving EOs at dose levels ranging from 75 to 1200 g/ton and observed that, on average, the performance improvement was 3 and 3% for weight gain and feed conversion, respectively, whereas many studies have reported a negative effect of EO on growth or feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, previous studies on broilers have shown that serum urea was not affected by thyme essential oil supplementation. [49][50][51] The observed reduction in renal function biomarkers, namely; creatinine and urea may be attributed mainly to the antioxidant properties of thyme which, like other plants in the Labiatae family, is a rich source of phenolic substances: phenolic acids (mainly rosmarinic acid) and flavonoids. The active compounds in thyme could have antiinflammatory properties and increase the activity of phase I and phase II xenobiotic detoxification enzymes, which would also promote hepatoprotection.…”
Section: Effect Of Thyme Essential Oil On Renal Function In Turkeysmentioning
confidence: 99%